2018
DOI: 10.1371/journal.pone.0200474
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin therapy reduces cardiac inflammation and mitigates adverse cardiac remodeling after myocardial infarction: Potential therapeutic targets in ischemic heart disease

Abstract: IntroductionAcute myocardial infarction (MI) is a primary cause of worldwide morbidity and mortality. Macrophages are fundamental components of post-MI inflammation. Pro-inflammatory macrophages can lead to adverse cardiac remodeling and heart failure while anti-inflammatory/reparative macrophages enhance tissue healing. Shifting the balance between pro-inflammatory and reparative macrophages post-MI is a novel therapeutic strategy. Azithromycin (AZM), a commonly used macrolide antibiotic, polarizes macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
2
37
0
Order By: Relevance
“…This result is also supported by previous studies that reported fewer patients with bacteremia among those who underwent SRP with oral AZM . The use of AZM also suppresses the production of cytokines, such as TNF‐α and IL‐6, which are involved in increasing body temperature, by dendritic cells . This may have inhibited the elevation of temperature in the experimental group.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This result is also supported by previous studies that reported fewer patients with bacteremia among those who underwent SRP with oral AZM . The use of AZM also suppresses the production of cytokines, such as TNF‐α and IL‐6, which are involved in increasing body temperature, by dendritic cells . This may have inhibited the elevation of temperature in the experimental group.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in the gingival crevicular fluid sample of the experimental group, the levels of several factors (hs‐CRP, IL‐6, and TNF‐α) improved significantly at 6 weeks postoperatively compared with the baseline. There has been a report that AZM suppresses inflammatory cytokines and alleviates inflammation ; therefore, it may have some sort of effect in alleviating inflammation in the acute to recovery phases. This issue requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline cardiac function was assessed as previously described. 18 A heating pad and rectal temperature probe were utilized to keep body temperature at 37°C during the experiment. Modified parasternal long-axis and short-axis was utilized to determine left ventricular function and volume in M-mode, twodimensional and Doppler echocardiography modes.…”
Section: Echocardiographymentioning
confidence: 99%
“…Immunohistochemical assessments were carried out on deparaffinized and rehydrated sections as previously described. 18 After deparaffinization, washing, TRIS heat induced epitope retrieval, and protein and streptavidin/biotin blocking, slides were incubated with primary antibody: Isolectin B4 (L-2140, Sigma, St. Louis, MO) overnight at 4°C. After washing, sections were incubated with secondary antibody conjugated to streptavidin-Alexa Fluor 568 (S11226, Thermo Fisher Scientific, Waltham, MA) for 30 minutes, and cover slipped with mounting medium containing DAPI counterstain (Vector #H-1200).…”
Section: Immunofluorescencementioning
confidence: 99%